2016
DOI: 10.13031/trans.59.11456
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Irrigation Amount and Timing on Alfalfa Nutritive Value

Abstract: ABSTRACT. Most hay producers in southwest Kansas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Our findings are supported by several previous investigations (Baral et al, 2022;Boyer, 1970;Diatta et al, 2021;Holman et al, 2016;Lindenmayer et al, 2011;Orloff et al, 2015;Peterson et al, 1992;Schneekloth & Andales, 2017;Shewmaker et al, 2011;Takele & Kallenbach, 2001;Undersander & Cosgrove, 2011), which found a positive correlation between alfalfa DMY and soil moisture. Schneekloth and Andales (2017), Shewmaker et al (2011), and Takele and Kallenbach (2001) claimed that alfalfa requires a significant amount of water compared to other field crops.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are supported by several previous investigations (Baral et al, 2022;Boyer, 1970;Diatta et al, 2021;Holman et al, 2016;Lindenmayer et al, 2011;Orloff et al, 2015;Peterson et al, 1992;Schneekloth & Andales, 2017;Shewmaker et al, 2011;Takele & Kallenbach, 2001;Undersander & Cosgrove, 2011), which found a positive correlation between alfalfa DMY and soil moisture. Schneekloth and Andales (2017), Shewmaker et al (2011), and Takele and Kallenbach (2001) claimed that alfalfa requires a significant amount of water compared to other field crops.…”
Section: Discussionsupporting
confidence: 92%
“…The correlation between soil moisture levels and CP content was negative but positive with ADF and NDF in a greenhouse experiment on alfalfa conducted in Quebec, Canada, by Petit et al (1992). This finding was further supported by field studies conducted in Southeast Kansas by Holman et al (2016) and in Northwest China by Li and Su (2017). Typically, when the concentrations of ADF and NDF increase, the consumption of forage tends to decrease.…”
Section: Discussionsupporting
confidence: 72%
“…Average nutritive value reported for canola in this study ( e.g., CP, ∼200 g kg −1 ; ADF, ∼340 g kg −1 ; relative feed value index, ∼150; and other nutritive value parameters) indicate that canola has relatively high nutritive value compared to annual forage grass species such as wheat (Holman et al, 2009(Holman et al, , 2010, forage sorghum (Sorghum bicolor [L.] Moench; Holman, Obour, & Mengel, 2019), oat (Avena L.; Obour, Holman, & Schlegel, 2019), and triticale (Obour, Holman, & Schlegel, 2020). The nutritive values reported for canola are comparable to ∼211, ∼316, and ∼422 g kg −1 CP, ADF, and NDF values, respectively, reported for alfalfa (Medicago sativa L.) forage (Holman, Min, Klocke, Kisekka, & Currie, 2016). Due to its greater relative feed value compared to wheat (Begna et al, 2017;Heer, 2006), canola has the potential to be a forage crop in rotation or in combination with winter wheat in the U.S. Great Plains and similar regions.…”
Section: Discussionmentioning
confidence: 75%
“…The introduced indicator of the alfalfa quality yield effectively evaluates the trade-off between quality content and hay yield under PRDSDI and CSDI, serving as a practical tool for informed decision-making at both the farm and policy levels. This indicator has found utility in forage field management and other natural grassland ecosystems ( Holman et al., 2016 ; Wang et al., 2020 ; Kamran et al., 2022 ), as well as in other natural grassland ecosystems ( Wang et al., 2011 ; Grant et al., 2014 ; Schaub et al., 2020 ; Li et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%